SEGMENTASI PREFERENSI BELANJA ONLINE MAHASISWA FEB UNIVERSITAS DUMAI: IMPLIKASI STRATEGI E-COMMERCE - Nisyah, Habibah Tun; Irvan, Puji Ananda; Kuntari, Oktarini; Rineliana, R.; Tampubolon, Omar Farrakhan (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to identify online shopping preference segments among students at the Faculty of Economics and Business, University of Dumai, based on demographic characteristics and digital lifestyle, and to provide strategic implications for e-commerce marketers. Employing a quantitative approach and cluster analysis, the research identifies three homogeneous student segments: (1) Pragmatic Shoppers, primarily evening class students who prioritize efficiency and functional value; (2) Digital Trend Followers, predominantly female morning/day class students significantly influenced by influencers and live shopping; and (3) Cautious Consumers, mainly fifth-semester students who are skeptical and focus on transaction security. These findings affirm that effective market segmentation in the digital era necessitates integrating demographic variables with digital lifestyle dimensions, such as social media engagement and digital literacy, to generate more accurate consumer profiles. The results contribute to digital marketing literature by providing a segmentation model specific to university students in a regional higher education context, offering practical guidance for marketers to design personalized, efficient, and competitive strategies.